Aspek Perlindungan Hukum dari Pendaftaran Tanah terhadap Pemegang Hak atas Tanah berdasarkan Pengaturan Akta Otentik sebagai Alat Pembuktian yang Sah - I Putu Arwan Puspa Resmawan; I Nyoman Alit Puspadma (Kertha Wicaksana, 2025)
Land registration is a form of state service that aims to provide legal certainty and protection for landowners in Indonesia. This paper analyzes the legal protection granted to landowners through land certificates and evaluates whether such certificates can be classified as authentic deeds (akta otentik) under Indonesian civil law. The study uses a normative legal research method, employing both statute and conceptual approaches. The statute approach examines relevant legal instruments such as the 1945 Constitution, the Basic Agrarian Law (Law No. 5/1960), and Government Regulation No. 24/1997 on Land Registration in conjunction with Government Regulation No. 18/2021. Meanwhile, the conceptual approach explores the theoretical foundation of legal certainty, ownership rights, and the evidentiary power of written documents in civil law. The findings reveal that land registration is a systematic and continuous state obligation, which culminates in the issuance of a land certificate. This certificate functions not only as evidence of ownership but also as a tool of legal protection, especially when disputes arise. Furthermore, based on Article 1868 of the Indonesian Civil Code, land certificates issued by the Land Affairs Office fulfill the criteria of authentic deeds, as they are created by authorized public officials in accordance with statutory procedures. Consequently, land certificates possess the highest evidentiary value in civil legal proceedings. The research contributes to understanding the dual administrative and legal functions of land certificates, reinforcing their status as both proof of ownership and instruments of legal certainty.